INNAVATSION TA’LIM TEXNOLOGIYALARI (STEAM TEXNOLOGIYASI) - S.P. Kutliyev; R.A. Vafoyev; K.F. Yarashov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abctract: This article presents the advantages and opportunities of using innovative educational technologies, STEAM technology, and innovative educational technologies in the classroom.